Medieval Worlds : a Sourcebook. - Anderson, Roberta (Taylor and Francis, 2013)
Complete with introductions, full commentary, glossary, and a guide to further reading, Medieval Worlds is a comprehensive sourcebook for the study of Western Europe from the fifth to the fifteenth century. Drawing on a wide range of documents, from chronicles, legal, state, and church documents, to biographies, poems, and letters from all over Europe, the authors expertly illustrate to the reader the unity - and complexity - of the medieval world. Amongst many more, central issues discussed include:the diverse world of monasteriesthe Papacy<LI.